Problemy adaptacji dziecka w okresie międzywojennym - Chodkowska, Maria; Bednarz-Grzybek, Renata (Biuletyn Historii Wychowania, 2016)
The study revolves around issues of child adaptation in the pedagogics of Janusz Korczak. The consecutive parts of the article focus on the problems of child adaptation to institutions i.e. orphaned children to educational centres as well as school conditions in general. The authors of the study pay close attention to the issue of child adaptation in his/her family and the local, urban and rural environments.